Development of Pedagogical Education in Theological Seminaries in the Russian Empire in 1866 - 1884 (On the Materials of the Ukrainian Gubernias) - T. Tverdokhlib (University of Sofia, 2019)
The article is focused on a specific aspect of history of men's secondary schools of the Orthodox Church theological seminaries, which functioned in the Ukrainian gubernias of the Russian Empire. Organization of pedagogical education in theological seminaries is established to be a prerequisite for suc-cessful teaching activity of their graduates. The paper reveals the content of pedagogical education in theological seminaries, knowledge, skills and abilities that students attained there within 1866-1884. The paper focuses on arranging seminarians teaching practice at daily, holiday and Sunday schools. The paper identifies the forms and methods of pedagogical education and requirements set up by the Holy Synod for organization of educational process in secondary theological educational institutions. The paper reveals the specific features of staffing and teaching and methodological support for teaching Pedagogy and concludes about the advantages and disadvantages of pedagogical education in theological seminaries and the level of pedagogical education compared to classical gymnasia.